Financial Considerations for Health and Safety in the Australian Dairy Industry. Issue 2 (3rd April 2017) - Lower, Tony; Pollock, Kirrily
ABSTRACT: Objective: This study aimed to quantify the burden of fatal and workers' compensation–related injuries on the dairy sector in Australia and to assess current financial inputs for work health and safety actions. Methods: The first and second phases entailed a review of the financial costs associated with fatal (2001–2013) and workers' compensation cases (2008–2009 to 2012–2013). The third element was a case-study approach focusing on actual production and cost data from a small sample of dairy farms ( n = 6) to ascertain an estimate for current financial inputs to work health and safety. Results: The estimated financial impact was approximately AUD$12.4 million each year, comprising AUD$6.8 million for fatalities and AUD$5.6 million for compensable injuries. All sample businesses were investing in health and safety initiatives; however, this was modest and on average represented 0.4% of total expenditure (AUD$4, 472) or <AUD$0.02 of the costs per kilogram of milk solids produced. When projected nationally, the inputs were around AUD$13.2 million annually. Conclusions: Despite data limitations, there is a compelling financial case to increase strategic investments into work health and safety by dairy farmers in Australia. Increased investment has the potential to not only minimize the burden of injury and costs to dairy farmers, but will also significantly reduce the devastating impacts that these incidents have on individuals, their families and communities.